Pendampingan Pemberdayaan Potensi Masyarakat dalam Bidang Pertanian dan Home Industry di Desa Butuh Kras Kediri pada Masa Pandemi Covid-19 - Umi Khoirun Nisa’; Khoirotul Izzah (Jurnal Pengabdian kepada Masyarakat Desa (JPMD), 2020)
Local potential is the wealth of Islam, culture, and human resources in an area. The potential of nature in a region depends on the geographical conditions, climate and landscape of the area. In this report entitled "Assistance in Empowering Community Potential in Agriculture and Home Industry in The Village Needs Kras Kediri During the Covid 19 Pandemic". This report discusses the assistance of the potential that the community has for the economic prosperity of the local community through agriculture and home industry. The type of method used in this report is the PAR (Participatory Action Research) method is a research that actively involves all parties who are willing (stakeholders) in reviewing ongoing actions (where their own experience as a problem) in order to make changes and improvements in a better direction. The goal is to assist and help the community to the efforts or activities carried out and provide awareness to the community of its potential so that it will be able to prosper the community economy in this Covid 19 pandemic. The results of pkm research activities, the author found that the process of mentoring the local potential of agriculture and home industry carried out by the community in developing the home industry by utilizing the local potential in the village needs Kras District, Kediri Regency in the form of SDA and HUMAN RESOURCES with the aim that the community has a useful potential and knows the conditions and opportunities so as to help improve the economy of the community.